Community-Based Tobacco Smoking Cessation Programmes Among Adolescents in Sarawak: Lesson Learned from Process Evaluation - Siddiq, Muhammad; Md Mizanur, Rahman; Sabrina, Lukas; Kamarudin, Kana; Merikan, Aren; Rudy Ngau, Ajeng; Mohd Faiz, Gahamat (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Abstract Introduction: This study evaluated the effectiveness of community-based quit-smoking interventions using the 5A’s and 3A’s modules.